2010
DOI: 10.1007/s13157-010-0040-z
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Integrated Constructed Wetlands (ICWs) to Enhance Macroinvertebrate Diversity in Agricultural Landscapes

Abstract: Integrated Constructed Wetlands (ICWs) constitute an alternative option for the treatment of agricultural wastewater in Ireland. These surface flow systems are formed by interconnected ponds and have the capacity to fit into the landscape and provide habitat for a wide range of biota, including macroinvertebrates that have enormous potential for biodiversity enhancement. For these reasons, five ICW systems were studied. In addition, five natural ponds were investigated to account for the potential of ICW ponds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…In this respect, Becerra-Jurado et al (2010) showed that permanent ICW ponds (around 5 years old) showed no significant seasonal differences (spring vs. summer) in coleopteran community structure, indicating low species turnover (lost and new pond species). In contrast, temporary ponds may act as sink habitats for taxa from permanent ponds via seasonal influx of aerial colonizers (Nilsson & Svensson, 1994).…”
Section: Macroinvertebrate Diversity Of Surface Flow Constructed Wetlmentioning
confidence: 93%
See 3 more Smart Citations
“…In this respect, Becerra-Jurado et al (2010) showed that permanent ICW ponds (around 5 years old) showed no significant seasonal differences (spring vs. summer) in coleopteran community structure, indicating low species turnover (lost and new pond species). In contrast, temporary ponds may act as sink habitats for taxa from permanent ponds via seasonal influx of aerial colonizers (Nilsson & Svensson, 1994).…”
Section: Macroinvertebrate Diversity Of Surface Flow Constructed Wetlmentioning
confidence: 93%
“…Amongst the biota present in surface flow constructed wetlands, birds have yielded the most extensive data series (Knight et al, 2001;Benyamine et al, 2002, Hansson et al, 2005, although macroinvertebrates have been a group also targeted in most of these biodiversity studies (Spieles & Mitsch, 2000;Knight et al, 2001;Hansson et al, 2005;Becerra-Jurado et al, 2010;Boets et al, 2011).…”
Section: Macroinvertebrate Diversity Of Surface Flow Constructed Wetlmentioning
confidence: 99%
See 2 more Smart Citations
“…Integrated Constructed Wetlands (ICW) are man-made wetlands (a series of interconnected ponds containing emergent and submerged plants) built to treat agricultural wastewater (Becerra-Jurado et al, 2010). They can ensure that ponds remain in agricultural landscapes and have been recorded to contribute significantly to freshwater biodiversity; total macroinvertebrate diversity in the last ponds of an ICW series (116 taxa) in Ireland was comparable to total diversity in natural ponds (129 taxa), although the ICW pond at the beginning of the series supported limited invertebrate biodiversity compared to the others (Becerra-Jurado et al, 2010).…”
Section: Agricultural Pondsmentioning
confidence: 99%